OP0176 Clusters of Single Nucleotide Polymorphisms Within the HLA-DRB1 Gene in Relation to Antibodies Against Citrullinated Peptides in Individuals Prior to the Development of Rheumatoid Arthritis. (23rd January 2014) - Rantapää Dahlqvist, S.; Ärlestig, L.; Brink, M.; Rönnelid, J.; Klareskog, L.
Abstract : Background: Multiplex analysis has demonstrated the presence of several antibodies against cyclic citrullinated peptides (ACPA) preceding the development of rheumatoid arthritis (RA) by several years. Certain HLA-DRB1* alleles are strongly associated with RA. Objectives: To relate the presence of different ACPA, in individuals before the onset of symptoms of RA, to single nucleotide polymorphisms (SNPs) within the HLA-DRB1 region in order to identify the SNPs most highly associated with the ACPAs analysed in the disease development. Methods: The study group comprised 406 individuals, with 717 samples, who were identified before the onset of symptoms (median (IQR) 7.4 (9.3) years), of 976 population controls, who were identified as donors to the Medical Biobank of Northern Sweden. Analysis of antibodies against 10 different citrullinated peptides in plasma using a microarray system developed in collaboration with Phadia AB/Thermofisher, Uppsala, based on their ISAC platform. The highest frequencies of antibodies were found for fibrinogen (Fib) ß36-52, CEP-1, and filaggrin. Samples from the same individuals (n=370) were genotyped with the Immunochip custom array according to Illumina protocols (SNP&SEQ Technology Platform, Uppsala, Sweden). 81 SNPs covering the HLA-DRB1* to DQA1* region were analysed. The Haploview software version 4.2 was used for haplotype and association analysis with a permutation test and cluster analysis (Bray-Curtis) was performed using Past software. Results: Thirty-seven of the SNPs were associated with the pre-diseased individuals compared with controls. After permutation test 22 of them and six haplotypes (7-16 SNPs) remained significantly associated. Anti-CEP-1 antibodies were associated with 15 SNPs although none remained significant after permutation tests. Anti-filaggrin antibodies were related to 4 SNPs, two of which were similar as for anti-CEP-1 (rs9271588 and rs9272363), none remained significant after permutation test. Anti-Fibß36-52 antibodies were associated with 4 different SNPs compared with the other antibodies and none was significant after permutation test. Antibodies against Fibß36-52 associated with the SNPs were all within the same cluster of SNPs, whilst associations of antibodies against CEP-1 were within three different sub-clusters. One cluster of SNPs was similar to where associations to anti- filaggrin were found. Conclusions: The presence of ACPA is related to a number of SNPs within the HLA- region albeit with somewhat different patterns between the various antibodies and clusters of SNPs. Disclosure of Interest: None Declared